EvidenceX: A Comprehensive Digital Forensics Tool for Evidence Extraction - Nakul Sharma; Sumit Minhas; Karanjit Singh; Vipin; Suman Hait; Lakshyaraj Singh Rathore (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
Background: Digital forensics operates as a core investigative element in present times since analysts need to examine metadata and prove file authenticity while locating hidden information. High-end file systems such as XFS and Btrfs include sophisticated features for journaling and copy-on-write that complicate the tasks of data forensic recovery as well as examination processes. Modern forensic tools focus on retrieving information but they demonstrate limited capability in producing extensive metadata analysis together with timeline reports. Investigative teams gain better results from checking times- tamps along with source device IDs and file historical logs to prove evidence authenticity compared to simply using deleted file recovery methods. File integrity remains secure because cryptographic hash values function as digital identification marks for authentication validation. Supplies of digital content with con- cealed data require identification to retrieve vital incriminating evidence. The modern forensic requirements have their solution in Evi- denceX which represents a state-of-the-art digital forensic utility. The system performs metadata extraction from multiple file types while automatically finding concealed content and analyzes both system logs and unusual behavior patterns simultaneously with steganography detection capabilities. Anomaly detection functionality in the system protects data consistency while the ”de-forensic” innovation allows secure metadata removal for privacy support. The present document examines how EvidenceX functions and demonstrates its operational value to boost digital forensic procedures through improved accuracy alongside effi- ciency and reliability aspects.